2013
DOI: 10.1007/s10584-013-0994-y
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal to yearly assessment of temperature and precipitation trends in the North Western Mediterranean Basin by dynamical downscaling of climate scenarios at high resolution (1971–2050)

Abstract: The complex topography and high climatic variability of the North Western Mediterranean Basin (NWMB) require a detailed assessment of climate change projections at high resolution. ECHAM5/MPIOM global climate projections for mid-21st century and three different emission scenarios are downscaled at 10 km resolution over the NWMB, using the WRF-ARW regional model. High resolution improves the spatial distribution of temperature and precipitation climatologies, with Pearson's correlation against observation being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
2
18
0
Order By: Relevance
“…In this context, Argüeso et al [] demonstrated the ability of the Weather Research and Forecasting (WRF) model to capture the frequency and the main spatial patterns of rainfall in Spain, which is the most important variable related to drought events. Regarding temperature, which is another key variable for droughts, Gonçalves et al [] have also shown the improvements provided by the dynamical downscaling based on WRF in terms of this variable in this topographically complex region.…”
Section: Introductionmentioning
confidence: 99%
“…In this context, Argüeso et al [] demonstrated the ability of the Weather Research and Forecasting (WRF) model to capture the frequency and the main spatial patterns of rainfall in Spain, which is the most important variable related to drought events. Regarding temperature, which is another key variable for droughts, Gonçalves et al [] have also shown the improvements provided by the dynamical downscaling based on WRF in terms of this variable in this topographically complex region.…”
Section: Introductionmentioning
confidence: 99%
“…and atmospheric research needs. The WRF models have been widely applied in regional simulations [Caldwell et al, 2009;Chotamonsak et al, 2011;Feng et al, 2012;Wang et al, 2012;Gonçalves et al, 2014], and their ability in climatological mean and extreme climate simulations over China has been tested and verified [Yu et al, 2010;Yang et al, 2012]. Moreover, WRF could improve the performance of interannual variations that are presented by its driving data [Yuan et al, 2012;Sato and Xue, 2013].…”
mentioning
confidence: 99%
“…The physical parameterisations selected for the representation of the different atmospheric processes and the computational simulations set-up are selected according to previous studies for the area [36,37]. Two one-way nested domains are defined over the area of interest, Fig.…”
Section: Modelling Systemmentioning
confidence: 99%
“…(1)), mainly as a consequence of the projected temperature changes. The surface air temperature in the NEIP is projected to increase [36]. The combined effect of those parameters in climate change scenarios could lead to changes up to À70 W m À2 (À20%) in wind energy density in coastal areas and mountain ranges of the NEIP for the A2 scenario (Fig.…”
Section: Wind and Energy Density Projectionsmentioning
confidence: 99%